ANALISIS EFISIENSI PELAYANAN RAWAT INAP DI TINJAU DARI INDIKATOR PELAYANAN RAWAT INAP PADA BLUD RSUD dr. H. SOEMARNO SOSROATMODJO KAPUAS TAHUN 2017 - Galih Persadha; Aus Al Anhar; Fakhrurrasyid Anshari (Politeknik Unggulan Kalimantan, 2019)
Activity that is routinely carried out al BLUD RSUD dr. H. Soemarno Sosroatmodjo Kapuas which calculate the efficiency of bed occupancy. Inpatient service indicators for the last 3 years have fluctuated but have not met the standards. The purpose of this research was to determine the efficiency of inpatient service based on indicators of inpatient service at BLUD RSUD dr. H. Soemarno Sosroatmodjo Kapuas in 2017. This type of research use descriptive quantitative cross sectional approach with observation method, namely observing and calculating directly in the field. Daily inpatient census from 00.00 to 24.00 at 08.00 is handed over to the medical record. In 2017 the BOR result 52,51%, AvLOS 2,30 days, TOI 2,99 days, and BTO 58 times. Based on the measurement of Barber Johnson Chart the BOR value in the efficient area is the Cempaka room, while VIP, Isolation, ICU, VK, Teratai, Mawar, Perinatology, Kenanga, Dahlia, and Anggrek are outside the area efficiently. BOR values under the Health Department standards and Barber Johnson need to be made efforts to improve the quality of services including by completing facilities and infrastructure and improving service quality and human resource skills to restore public confidence in the hospital.